The Payments System and its Effectson Monetary Operations : Recent Experience in the Russian Federation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1994)
Recent developments and reforms in the Russian payments system are discussed from the perspective of their impact on monetary policy. The large and highly variable payment float in the balance sheet of the Central Bank of Russia has complicated the conduct of monetary policy. However, reforms in late 1992 and early 1993 have been effective, as judged from their impact in reducing the level and variability of float, and have set the stage for medium-term reforms of the payments system. Rapid progress in the implementation of these reforms, and their appropriate coordination with monetary operations, remain critical to meet the emerging needs in money and foreign exchange markets, and to support the transition to indirect methods of monetary control.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet